Tethered drone control - Loke, Jie Jun (Nanyang Technological University, 2024)
Drones are the result of advancements in technology, especially in the field of robotics. Small, lightweight multirotor drones are popular and in high demand due to their portability, affordability, and ease of control. However, they usually have low flight endurance as they operate with an onboard Lithium Polymer (LiPo) battery. Weight is also one of the limitations of these drones since they have low carrying capacity compared to larger ones.